Chapter Dante nella poesia ucraina del Novecento. L'esperienza di due generazioni - Rekut-Liberatore, Oleksandra (Biblioteca di Studi di Filologia Moderna, 2022)
It is not a heavenly, but rather a hellish Dante, who hovers over Ukrainian poetry of the twentieth century. He supports the persecuted rather than the adepts of the Soviet regime, who are mere functionaries. Dante leads the way for the stoic Ukrainian poets, such as Mykola Zerov, Iurij Klen, Vasyl' Stus, and Lina Kostenko, who are fully aware of the risks they take in aspiring to longed-for moral freedom.